2017
DOI: 10.1007/s00586-017-5061-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of thoracic posterior vertebral column resection for severe congenital spinal deformities

Abstract: Thoracic PVCR can lead to satisfactory outcomes in the treatment of severe spinal deformities. Risk factors for neurological complications include the age over 18 years, presence of pulmonary dysfunction, and EBL greater than 50%. The pulmonary dysfunction can be regarded as the most valuable indicator to measure the severity of the spine deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…Previous investigators reported that the incidence of neurological problem was from 1.2% to 17.1%. [ 8 , 20 23 ] In our series, the neurological complication occurred only in group 1, which followed unexpected additional operation in all of the cases. In group 1, the additional operation was significantly more than group 2 (13 and 3 cases, P = .007).…”
Section: Discussionmentioning
confidence: 53%
“…Previous investigators reported that the incidence of neurological problem was from 1.2% to 17.1%. [ 8 , 20 23 ] In our series, the neurological complication occurred only in group 1, which followed unexpected additional operation in all of the cases. In group 1, the additional operation was significantly more than group 2 (13 and 3 cases, P = .007).…”
Section: Discussionmentioning
confidence: 53%
“…CS is one of the most difficult type of early onset scoliosis to manage. This congenital vertebral defect can lead to significant spine deformities, which occasionally present as rigid, severe curvature requiring osteotomy (e.g., SPO, PSO or VCR) to obtain global balance of the spine [ 9 11 ]. CS is also often associated with anomalies in other organs, which may be isolated or in association with the VACTERL (vertebral anomalies, anorectal atresia, cardiac anomalies, tracheoesophageal fistula, esophageal atresia, renal and limb anomalies) syndrome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…PVCR is a surgically demanding technique with a high complication rate (40–67%) after surgery [ 6 , 10 , 25 ]. Neurologic complications are reported in 1.2–17.1% of patients [ 5 , 15 , 20 , 26 ]. Because of these problems, surgeons should evaluate the risks and share the information with patients or their guardians before surgery.…”
Section: Discussionmentioning
confidence: 99%